Observation of stroke in a tertiary care neurology and neurosurgery hospital in Bangladesh: risk factors, symptoms and treatment strategies - Khanam, Umme Salma (BRAC Univeristy, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2018.